Association between caregiving, meaning in life, and life satisfaction beyond 50 in an Asian sample : age as a moderator - Ang, Rebecca P. (2013)
The association between caregiving, meaning in life, and life satisfaction was examined in sample of 519 older Asian adults beyond 50 years of age. Two hierarchical multiple regression analyses were conducted to examine age as moderator of the associations between caregiving, meaning in life, and life satisfaction. Age moderated the association between caregiving and life satisfaction; the association between caregiving and life satisfaction was statistically significant for the middle adulthood group but not for the late adulthood group. Age moderated the association between meaning in life and life satisfaction; the association between meaning in life and life satisfaction was statistically significant for both groups, but it was stronger in magnitude for the late adulthood group compared to the middle adulthood group. These findings highlight that there are certain key developmental tasks encountered by individuals at the middle and late adulthood stages, and that these distinctive relevant tasks at various developmental stages differentially predict individuals’ life satisfaction in an Asian sample.